HUBUNGAN KEPRIBADIAN DENGAN HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMA NEGERI 9 PONTIANAK - Rozi, Fahru; Hidasari, Fitriana Puspa; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe problems discussed in this study are the behavior of students who deviate, especially to teachers outside the physical education, the behavior of students who are rude towards peers, and deviant behavior towards the environment. The purpose of this study was to determine the Relationship between Personality and Physical Education Learning Outcomes in Sport and Health in SMA Negeri 9 Pontianak. Descriptive research method involving two variables, namely the independent variable Personality and the dependent variable, namely the learning outcomes of physical education and sports. population of class XI students of SMA Negeri 9 Pontianak consisting of 6 classes, sampling using a random sampling method, researchers took one class of the total population, with a total sample of 36 students. This research technique uses tests and measurements, namely tests with a lattice measuring instrument of personality with physical education learning outcomes. Data analysis uses the correlation formula. The results of this study indicate that there is a personality relationship with the learning outcomes of physical and health physical education in SMA Negeri 9 Pontianak. This can be proven based on the calculation results, where the calculated value is 0.522> rtable value (0.339), so that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means that there is a personality relationship with the learning outcomes of physical education and sports in health at SMA Negeri 9 Pontianak.Keywords: Learning outcomes, Personality.